PENERAPAN METODE KOOPERATIF LEARNING TIPE TWO STAY TWO STRAY DAN PERMAINAN KALIMAT BERANTAI UNTUK MENINGKATKAN KETERAMPILAN MENULIS KARANGAN BERDASARKAN PENGALAMAN - Erfiana, Eka; Sunarya, Dede Tatang; Irawati, Riana (Jurnal Pena Ilmiah, 2017)
Skill writing is one of the language is to be controlled by students in subject of indonesian language .Writing skills taught that students have skills write a good one and can be taken as a means of communication in the life of everyday . One methods used to teach write that is practicing cooperative type two stay two stray and game sentence chain .Through the two are two stray and game sentence chain , students will know procedures for writing with regard to penggunan spelling with well as learning bepleasant .But in fact he is not all teachers able to teach writing skills correctly .This article will talk about the application of the cooperative type two stay two stray and game chain sentence to improve writing skills of from experience on the kids grade school district 1 danamulya plumbon cirebon.